The Role of Health Counseling in Increasing Students' Knowledge About The Impact Of Gadget Use - Lombogia, Moudy; Karundeng, Yanni; Lapian, Rubie Christine; Pasambo, Yourisna (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2022)
Background: More than 100 million people in Indonesia use gadgets, both adults, teenagers, and children. In addition to the positive impact, gadgets also have many negative impacts. For teenagers, excessive use of gadgets can cause them to become forgetful of time, lazy, cyber bullying, insomnia, nomophobia, as well as tend to make teenagers become individualistic. The purpose of this study is to determine the influence of health counseling about the impact of gadget use on the knowledge of students of SMP Negeri 8 Manado. Method: The type of research is preexperimental with the form of One Group Pretest Posttest Design to compare knowledge before and after being given health counseling about the impact of using gadgets. The research population is all students of SMP Negeri 8 Manado. The sampling technique uses purposive sampling with a total sample of 46 respondents. The data analysis used is univariate analysis and bivariate analysis using the Wilcoxon Signed Rank Test. Result: The Wilcoxon test showed p-value = 0.000 (≤ 0.05). There are differences in adolescents' knowledge before and after being given counseling about the impact of using gadgets. Conclusion : Health counseling about the impact of using gadgets increases students' knowledge at SMP Negeri 8 Manado. The advice for students at SMP Negeri 8 Manado is that they are expected to be able to use gadgets more wisely so that the negative impact of gadgets can be avoided.